Thryroid Hormones and Hematological Indices Levels in Thyroid Disorders Patients at Moi Teaching and Referral Hospital, Western Kenya. (15th April 2013) - Iddah, M. A.; Macharia, B. N.; Ng'wena, A. G.; Keter, A.; Ofulla, A. V. O.
Abstract : Problem Statement . Thyroid disorders are prevalent in western Kenya, but the effects of disorders on thyroid hormones and hematological indices levels have not been documented. Study Population . Patients treated for thyroid disorders at the MTRH between January 2008 and December 2011. Objectives . To determine the thyroid hormones and hematological indices levels in thyroid disorders patients at the MTRH, western Kenya. Methodology . A retrospective study in which patient data and stored samples of patients, who presented with thyroid pathologies, underwent thyroidectomy, and histological examinations are done. Thyroid stimulating hormone (TSH), thyroxine (T4 ), and triiodothyronine (T3 ) blood levels, white blood cells (WBCs), red blood cells (RBCs), platelet counts, and hemoglobin (Hb) levels were analyzed. Results . Male : female ratio was 1 : 10.9 with female representing 368 (95%). The median age was 41 (IQR: 32–48) with a range of 14–89 years. HHormonal levels for immunological thyroid disease patients were higher (P = 0.0232 ; 0.040) for TSH and (T3 ) for those aged 30–39 years, respectively. The WBCs, RBCs, HGB, and platelets in immunological thyroid disease were not statistically significant with P values of 0.547, 0.205, 0.291, and 0.488 respectively. Conclusion . The presence of anaemia due to low RBCs in thyroid disease is not significantly associated with thyroid hormone with a P value of 0.512.